Design, synthesis and evaluation of novel anti-HCV molecules that deliver intracellularly three highly potent NS5A inhibitors. Issue 17 (1st September 2015) - Boucle, Sebastien; Tao, Sijia; Amblard, Franck; Stanton, Richard A.; Nettles, James H.; Li, Chengwei; McBrayer, Tamara R.; Whitaker, Tony; Coats, Steven J.; Schinazi, Raymond F.
Graphical abstract